Factors influencing the use of tocilizumab as monotherapy in patients with rheumatoid arthritis in a real-life setting: results at 1 year of the ACT-SOLO study. Issue 1 (10th January 2017) - Flipo, René-Marc; Maillefert, Jean-Francis; Chazerain, Pascal; Idier, Isabelle; Coudert, Mathieu; Tebib, Jacques
Abstract : Introduction: Using a biologic disease-modifying antirheumatic drug (bDMARD) as monotherapy in clinical practice for patients with rheumatoid arthritis (RA) is common and recognised by health authorities although current guidelines recommend to combine them with conventional synthetic (cs)DMARDs. This study mainly aimed to search for real-life factors influencing the use of tocilizumab as MONO or in combination (COMBO). Methods: In this non-interventional, prospective, national, multicentre study, data were collected every 3 months over a 12-month period in RA patients starting tocilizumab. The proportion of monotherapy patients was described, together with significant explicative factors. Results: Among the 577 analysed patients recruited from January 2012 to August 2013 (228 monotherapy patients; 40%), 79% were women, mean RA duration was 11±9 years, previous RA treatments included bDMARDs and csDMARDs in 75% of cases and mean Disease Activity Score 28 joints-Erythrocyte Sedimentation Rate (DAS28-ESR) was 5.2±1.3 at inclusion. Explicative factors for monotherapy were at least 65 years (OR=1.47, p=0.0485), no methotrexate within the two last years (OR=5.96, p<0.0001), past severe infection (OR=1.99, p=0.0272) and higher baseline DAS28-ESR (OR=1.22, p=0.0086). Regarding clinical results (DAS28-ESR, Clinical Disease Activity Index (CDAI) and Simple Disease Activity Index (SDAI) low disease activity and remission; ACR20/50/70 and European League Against Rheumatism (EULAR) response; Health Assessment Questionnaire Disability Index (HAQ-DI) score), no relevant differences between monotherapy and combination patients were observed at 1 year. A total of 23 tocilizumab-treated patients (4%) experienced serious infections; no new safety signals were noted with no differences between groups. Conclusions: ACT-SOLO confirms the high proportion of RA patients receiving tocilizumab as MONO in clinical practice. The study also showed that clinical results at 1 year were similar between MONO and COMBO patients in a real-life setting. Trial registration number: NCT01474291 .